Characterization, Kinetic Using Deconvolution Techniques and Thermodynamic Study of Synthetic MgHPO43H2O - Saifon Kullyakool; Somphob Thompho; Banjong Boonchom; Pesak Rungrojchaipon (My University, 2023)
MgHPO4·3H2O was synthesized via a simple wet reaction and transformed to its final decomposed product, Mg2P2O7 at 873 K. The thermal properties, vibrational modes of block units, and solid phases of the synthetic compounds have been investigated by TG/DTG/DTA, FTIR, and XRD techniques. The temperature dependence of thermodynamic properties estimated from the DSC data occurred in two regions (before and after the dehydration reaction) indicating a characteristic of the prepared MgHPO4·3H2O sample. The dehydration reactions of 3.5 mol of water molecules in the structure overlapped in the temperature of 363–823 K and showed the phase transition at 921 K as revealed by TG/DTG/DTA. The deconvolution technique using the newly modified co-mathematical functions was used to separate the overlapped dehydration steps in the DTG curve, which obtained the three steps. Only the first and second steps were estimated using kinetic triplet parameters (Ea, A, and model), which indicate the single dehydration mechanism with the A1.25 model and the multi-step of a parallel mechanism with the A1.6 model, respectively. The data of kinetics and thermodynamics play key points in theoretical study, application development, and industrial production of magnesium phosphates as a theoretical basis.
Keywords: Dehydration reaction; Thermal and Kinetic Analysis